POSSIBILITIES OF INCREASING OIL CONTENT IN SUNFLOWER BASED ON CRISPR/CAS9 TECHNOLOGY: https://doi.org/10.5281/zenodo.15177146 - Turayev , O.S.; Teshayeva , F.I.; Eshonkulova , D.Sh. (International scientific and practical conference, 2025)
This thesis analyzes the potential of increasing oil content in sunflower (Helianthus annuus L.) using CRISPR/Cas9 technology. Sunflower is a key crop in the food industry due to its high oil content and beneficial fatty acid composition. CRISPR/Cas9 technology is an advanced biotechnology that enables precise and efficient modification of plant genomes. The thesis examines the scientific basis and practical achievements of modifying genes that negatively influence oil content, specifically the modification of FAD2, FAD3, DGAT1, and WRI1 genes. These methods can be applied to improve the quality and efficiency of sunflower cultivation.